Responses and tolerance to high ammonium levels of hybrid Napier grass (Pennisetum purpureum × pennisetum americanum cv. Pakchong 1): Assessing the potential for water treatment and agricultural management in Southeast Asia - Tarvorasak V. (2017)
© 2016, Chiang Mai University. All rights reserved. The ability of hybrid Napier grass (Pennisetum purpureum x P. americanum cv. Pakchong 1) to grow under high NH 4 + concentrations was investigated. The plants were grown on a growth medium with five concentrations of NH 4 + (0.5, 1, 5, 10 and 15 mM) under greenhouse conditions. A positive response was found in the plants grown on the medium with 0.5-5 mM NH 4 + in which their growth rates and shoot elongation rates ranged from 0.4 to 0.5 g d -1 and 4.0 to 5.0 mm d -1 , respectively. At high NH 4 + concentrations (10 and 15 mM), the plant growth rates, root length and new shoot production decreased while leaf area increased. The stomatal index on both sides of the leaves was not significantly different among the treatments. Even though the NH 4 + concentration in the rooting medium did not affect its uptake by these plants, there was a decrease in NH 4 + content in the plant tissue after exposure to high NH 4 + levels. Similar results were also found for the levels of chlorophyll and some mineral nutrients, such as Ca, K and P. We conclude that, this species could tolerate high NH 4 + concentrations (up to 5 mM). It still grew well and had high N accumulation in the tissue. This property suggests that the hybrid Napier grass may have a potential for removing inorganic nitrogen particularly NH 4 + from wastewater. In addition, high N accumulation in the tissue makes the plants good for animal feed after being harvested.